2010
DOI: 10.1080/19440040903571762
|View full text |Cite
|
Sign up to set email alerts
|

Descriptive modelling to predict deoxynivalenol in winter wheat in the Netherlands

Abstract: Predictions of deoxynivalenol (DON) content in wheat at harvest can be useful for decision-making by stakeholders of the wheat feed and food supply chain. The objective of the current research was to develop quantitative predictive models for DON in mature winter wheat in the Netherlands for two specific groups of end-users. One model was developed for use by farmers in underpinning Fusarium spp. disease management, specifically the application of fungicides around wheat flowering (model A). The second model w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
63
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 53 publications
(66 citation statements)
references
References 28 publications
1
63
2
Order By: Relevance
“…A comparison between samples collected by hand before harvest and machineharvested samples revealed that the method provided a good estimate of DON concentration at harvest. Mean DON content showed considerable variation between the years as described in other European regions (Isebaert et al 2009;Van Der Felz-Klerx et al 2010). In order to help the industry to limit potential food or feed safety problems, a tool based on weather conditions near anthesis was developed to define the annual risk of DON contamination.…”
Section: Discussionmentioning
confidence: 99%
“…A comparison between samples collected by hand before harvest and machineharvested samples revealed that the method provided a good estimate of DON concentration at harvest. Mean DON content showed considerable variation between the years as described in other European regions (Isebaert et al 2009;Van Der Felz-Klerx et al 2010). In order to help the industry to limit potential food or feed safety problems, a tool based on weather conditions near anthesis was developed to define the annual risk of DON contamination.…”
Section: Discussionmentioning
confidence: 99%
“…What became clearer with the BRT partial-dependence plots (and previously unnoticed) was the large jump in the risk of major FHB epidemics with mean RH ≥ 70% for these three group 7 preanthesis predictors. In fact, most FHB predictive models to date have used RH-type predictors based on RH ≥ 80 to 85% (7,31,39,41,47,54) or RH ≥ 90% (13,23). Notable exceptions are the use of an RH > 75% criterion by Schaafsma and Hooker (48) in toxin prediction in winter wheat and an RH ≥ 70% criterion in toxin prediction in oat (57) and wheat (58) in Europe.…”
Section: Discussionmentioning
confidence: 99%
“…In one sense, averaging the brt i models represented an intermediary step on the way to the brt u model, which was developed using predictors across all windows. Although BRTs and model averaging were promising, we can surmise from the wider cumulative modeling efforts to date (12,13,25,30,39,47,48,54,58) that no one modeling algorithm is likely to suffice in describing or predicting the highly sporadic FHB epidemics (26). As more algorithms are considered, FHB researchers may do well to consider ensemble prediction methods which combine several algorithms into a single predictive algorithm (46).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations